ANALISIS HARGA POKOK PRODUKSI MENGGUNAKAN METODE FULL COSTING DALAM PENETAPAN HARGA JUAL - EKO PURWANTO (Pusat P2M Politeknik Negeri Batam, 2020)
ABSTRACT Calculation of the cost of production is an important thing to note, because of the increasing competition between UMKM in producing quality products at quite competitive prices. This purpose of this research is to know how to calculated of the cost of goods manufactured to determine yhe selling price at UMKM Regar Fruit. Full costing method is a methode of dtermining the cost of goods manufactured which calculate all the elements from cost production which consist of materials cost, direct labour, factory overhead cost, both fixed cost and variable cost. The selling price can be obtained from cost of goods manufactured plus expected profit. The data used are primary data and secondary data. Primary data were obtained from the interview process through social media conducted with the ownes of UMKM. Secondary data obtained from UMKM Regar Fruit. The results of the research stated that the calculation of the cost of goods manufactured a difference that affected the selling price.